Obraz sarmatyzmu utrwalony w polskiej leksyce i przestrzeni społecznej – wybrane zagadnienia i przykłady - Filip, Grażyna; Patro-Kucab, Magdalena (Słowo. Studia językoznawcze, 2013)
The first part of this article is related to the cultural and literary background of Polish Sarmatism, a mythic ideology according to which Poles were descended from the ancient tribe of Sarmatians who inhabited the territory of present-day Ukraine between the 1 st and 4 th century. Such theories, constructed by the sixteenth-century historians, lasted until Romanticism and served the purpose of ennobling the nation’s history. The splendour of Sarmatian model was reviewed in the Enlightenment period. In the paper, examples of such criticism are given, derived from comedies by F. Bohomolec and F. Zabłocki. In the linguistic part of these considerations, the issues of language sociology and psychology are discussed. The definitions of a Sarmatian and Sarmatism, taken from various Polish dictionaries, are analysed. Lexical features listed there contributed to a stereotype perpetuated by the Enlightenment critique in subsequent lexicons. It ought to be mentioned that contemporary references to the climate and charm of the old Sarmatian days are deprived of specific negative characteristics.